Komentar Netizen Menjadi Hakim: Krisis Objektivitas Penegakan Hukum Pidana Akibat Dominasi Opini Publik - Jamaludin, Jamaludin; Tata Eliestiana Dyah A (RETORIKA: Journal of Law, Social, and Humanities, 2026)
Abstract The development of information technology and social media has driven the dominance of digital public opinion in criminal law enforcement in Indonesia, including the practice of trial by netizens, which has the potential to shift the objectivity, independence, and rationality of the justice system. This study aims to analyze the extent to which the dominance of public opinion shifts the objectivity of criminal law enforcement and how the phenomenon of trial by netizens triggers a crisis of objectivity in the criminal justice system. This study uses a normative legal research method with a statutory approach, a case approach, and a conceptual approach. The types and sources of legal materials are primary, secondary, and tertiary legal materials. The legal material collection technique is carried out through literature studies and analyzed qualitatively using legal reasoning and interpretation methods. The research results show that the dominance of public opinion in mass and social media has the potential to shift the objectivity of criminal law enforcement, because massive public pressure encourages law enforcement to be more responsive to social demands than to the principles of legality, presumption of innocence, and legal proof, thus risking weakening due process, judicial independence, and the objectives of the New Criminal Code for sentencing, which emphasize justice and human dignity. The phenomenon of trial by netizens shows that the digital space has transformed into an arena for social judgment that precedes the formal judicial process. Public opinion that goes viral on social media has the potential to suppress the objectivity of law enforcement, influence the decisions of law enforcement officers, and reduce the independence of judges. This condition also risks weakening the principles of due process of law and the protection of human rights, thus presenting a crisis of objectivity in the criminal justice system. Keywords: Netizen Comments; Judges; Objectivity Crisis; Criminal Law Enforcement; Public Opinion Dominance